Real wage cyclicality in Germany and the UK: new results using panel data - Fei Peng; William Stanley Siebert (Institute for the Study of Labor (IZA), 2007)
This paper compares the cyclical behaviour of male real wages in Germany and the UK using the German Socio-Economic Panel 1984-2002 and the British Household Panel Survey 1991-2004. We distinguish between job stayers (remaining in the same job), and within- and between-company job movers. Stayers are the large majority in both countries. Using changes in the unemployment rate as the cyclical measure, we find real wages of stayers in the private sector in West Germany but not East Germany to be procyclical, and quite sensitive to unemployment, comparable to the US and the UK. We find cyclicality in the public sector in neither country. Thus real wage flexibility is similar in the two countries, apart from East Germany, despite apparent differences in wage-setting institutions.
urn:nbn:de:101:1-20080410298
Keywords: 330; Reallohn; Konjunkturelle Arbeitslosigkeit; Betriebszugehörigkeit; Arbeitsmobilität; Vergleich; Deutschland; Großbritannien